2015
DOI: 10.1590/s1983-41952015000400009
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of granular rubber waste tire reinforced soil for application in geosynthetic reinforced soil wall

Abstract: Large quantities of waste tires are released to the environment in an undesirable way. The potential use of this waste material in geotechnical applications can contribute to reducing the tire disposal problem and to improve strength and deformation characteristics of soils. This paper presents a laboratory study on the effect of granular rubber waste tire on the physical properties of a clayey soil. Compaction tests using standard effort and consolidated-drained triaxial tests were run on soil and mixtures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
1
4
0
3
Order By: Relevance
“…In addition, Hambriao and Pakaraddi (2014) reviewed the methods of soil improvement using different materials [20]. Behaviour of tire granule in geosynthetic reinforced soil wall were investigated by Ramirez et al (2015) [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Hambriao and Pakaraddi (2014) reviewed the methods of soil improvement using different materials [20]. Behaviour of tire granule in geosynthetic reinforced soil wall were investigated by Ramirez et al (2015) [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In turn, Ramirez et al [18], also in CD triaxial tests, have shown a significant impact of confining stress value on the shear strength of clay with granulate mixture. The strengthening of material was highest for the confining stress of 100 kPa at 10% addition of granulate, while for 400 kPa, the shear strength slightly diminished, whereas different behaviors are observed in direct shear tests.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The majority of research carried out on waste is directed primarily towards checking their influence on a change of the optimum moisture content in soils [17,18], on the mechanical behavior of soils [19][20][21][22][23], on the reduction of Atterberg's limits and plasticity index of fine-grained soils [21,[24][25][26], and on the reduction of natural soils swelling [16,[27][28][29][30]. If the first two groups of issues apply to all soils, then the next two are strictly related to cohesive (frequently expansive) soils.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given that empirical models/correlations are purely data-driven, their predictive capability is highly dependent on the database from which they are developed. Accordingly, to establish practical empirical models for the OMC and MDUW of soil-TDA blends, a large and diverse database of 100 soil-TDA compaction tests was gathered from the authors' previous publications [19,22,23,34,35] as well as other recent literature sources [15][16][17][36][37][38][39]. Detailed descriptions of the assembled database are presented in Tables 1 and 2.…”
Section: Database Of Soil-tda Compaction Testsmentioning
confidence: 99%